Galendo as A Traditional Foods of Ciamis - Fatimah Dwi Krisna Ayu; Ade Juwaedah; Elly Lasmanawati (Universitas Pendidikan Indonesia (UPI), 2022)
Galendo is a food made from coconut and has become part of the culture and traditions of Ciamis Regency. The existence of this galendo is passed down from generation to generation orally and informal learning. This research aims to obtain an overview of the history, the recipe for the formula for making galendo, and the efforts of informants in marketing their products. The research method used is a qualitative approach. The research data source is the primary data source with the research design used is descriptive qualitative. The author uses interview, observation, and documentation methods. Therefore, the instruments needed are observation guides, interview guides, tape recorders, cameras and stationery to support research. The results showed that the history of galendo's existence began with the movement to plant coconut trees on a large scale in Ciamis in the 1800s which resulted in many coconut trees growing. the main use of coconut in Ciamis is as an ingredient for making coconut oil. One of the traditional galendo factory businesses located in Pawindan Village, namely Galendo Tri Putra, This factory is one of the galendo suppliers in the Ciamis traditional market. Galendo is only made from coconut milk which is heated while stirring, then the precipitate called “oil dung” is filtered, wrapped in woven bamboo called sawuk and finally compacted to become galendo. Galendo is considered a valuable national cultural asset, the existence of this traditional food should not be lost with time.